Mercury concentration in phytoplankton in response to warming of an autumn – winter season. (August 2016) - Bełdowska, Magdalena; Kobos, Justyna
Abstract: Among other climate changes in the southern Baltic, there is a tendency towards warming, especially in autumn-winter. As a result, the ice cover on the coastal zone often fails to occur. This is conducive to the thriving of phytoplankton, in which metals, including mercury, can be accumulated. The dry deposition of atmospheric Hg during heating seasons is more intense than in non-heating seasons, owing to the combustion of fossil fuels for heating purposes. This has resulted in studies into the role of phytoplankton in the introduction of Hg into the first link of trophic chain, as a function of autumn and winter warming in the coastal zone of the lagoon. The studies were conducted at two stations in the coastal zone of the southern Baltic, in the Puck Lagoon, between December 2011 and May 2013. The obtained results show that, in the estuary region, the lack of ice cover can lead to a 30% increase and during an "extremely warm" autumn and winter an increase of up to three-fold in the mean annual Hg pool in phytoplankton (mass of Hg in phytoplankton per liter of seawater). The Hg content in phytoplankton was higher when Mesodinium rubrum was prevalent in the biomass, while the proportion of dinoflagellates was small. Highlights: A lack of icing led to a 30% increase of the mean Hg concentration in algae biomass. A warmer cold season led to a higher load of Hg introduce to the trophic chain. Mesodiunium rubrum accumulate mercury very effectively. Abstract : The warming of an autumn-winter season leads to lack of icing in the lagoon which contributes to the lengthening of the vegetation period and increases the mean annual Hg pool in phytoplankton, especially in presence of Mesodinium rubrum .